Phototrophic Fe(II)-oxidation in the chemocline of a ferruginous meromictic lake - Walter, Xavier A.; Picazo, Antonio; Miracle, Maria R.; Vicente, Eduardo; Camacho, Antonio; Aragno, Michel; Zopfi, Jakob (Frontiers in Microbiology, 2014)
Precambrian Banded Iron Formation (BIF) deposition was conventionally attributed to the precipitation of iron-oxides resulting from the abiotic reaction of ferrous iron (Fe(II)) with photosynthetically-produced oxygen. Earliest traces of oxygen date from 2.7 Ga, thus raising questions as to what may have caused BIF precipitation before oxygenic photosynthesis evolved. The discovery of anoxygenic phototrophic bacteria thriving through the oxidation of Fe(II) has provided support for a biological origin for some BIFs, but despite reports suggesting that anoxygenic phototrophs may oxidize Fe(II) in the environment, a model ecosystem of an ancient ocean where they are demonstrably active was lacking. Here we show that anoxygenic phototrophic bacteria contribute to Fe(II) oxidation in the water column of the ferruginous sulfate-poor, meromictic lake La Cruz (Spain). We observed in-situ photoferrotrophic activity through stimulation of phototrophic carbon uptake in the presence of Fe(II), and determined light-dependent Fe(II)-oxidation by the natural chemocline microbiota. Moreover, a photoferrotrophic bacterium most closely related to Chlorobium ferrooxidans was enriched from the ferruginous water column. Our study for the first time demonstrates a direct link between anoxygenic photoferrotrophy and the anoxic precipitation of Fe(III)-oxides in a ferruginous water column, providing a plausible mechanism for the bacterial origin of BIF’s before the advent of free oxygen.